1981
DOI: 10.1302/0301-620x.63b2.7217136
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of deep vein thrombosis of the leg in children on halo-femoral traction

Abstract: This prospective study was performed to determine the true incidence of deep vein thrombosis of the lower limb in children who had undergone halo-femoral traction to correct scoliosis before operation. Bilateral ascending phlebography of the lower limbs was performed on 54 children two days before spinal fusion and Harrington rod instrumentation. Two patients developed clinical evidence of thrombosis whilst on traction. This diagnosis was confirmed by phlebography. The other 52 children had no clinical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, some problems remain, principally complications associated with iliac puncture; this is associated with risks of damage to the main nerves or large blood vessels, causing paralysis or death [39,40]. Stiffness and early cervical spine degeneration were evident in almost all patients of HPT [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, some problems remain, principally complications associated with iliac puncture; this is associated with risks of damage to the main nerves or large blood vessels, causing paralysis or death [39,40]. Stiffness and early cervical spine degeneration were evident in almost all patients of HPT [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies including only pediatric orthopaedic trauma patients found a VTE incidence that ranged from 0 to 387 per 10,000 children 14,36 . Our meta-analysis found that VTE incidence was much higher in orthopaedic trauma surgery (29 per 10,000 children) compared with elective orthopaedic surgery (14 per 10,000 children) 14,15,[24][25][26][27][29][30][31][32][33][34][36][37][38][39]42,43,[45][46][47][48][49] . In our study, the median age of pediatric orthopaedic VTE patients was 13 years, which is older than in previous studies investigating pediatric VTE for all hospitalized patients.…”
Section: Discussionmentioning
confidence: 75%
“…A total of 2,467,764 pediatric patients were included in the 30 studies 4,13-15,24-49 , and 3,113 were diagnosed with VTE (Table I). After applying our study exclusions, the remaining 26 studies had 850,268 orthopaedic patients with 1,108 cases of VTE.…”
Section: Resultsmentioning
confidence: 99%
“…In one small prospective study, 4 of 54 children on halo-femoral traction had DVT [14]. This is in contrast to the incidence of DVT in hospitalized adults who received no prophylaxis (from 30 % overall in high-risk patients [15,16] to 40-60 % in adults with a hip fracture or arthroplasty [17][18][19]).…”
Section: Discussionmentioning
confidence: 97%